Apoptotic and autophagic cell death induced in cervical cancer cells by a dual specific oncolytic adenovirus. Issue 3 (17th November 2022) - Li, Shanzhi; Li, Zhuoxin; Chen, Shuang; Zhu, Yilong; Li, Yiquan; Yin, Xunzhe; Li, Xiao; Zhu, Guangze
Abstract : Objective: Oncolytic adenoviruses are capable of exerting anticancer effects via a variety of mechanisms, including apoptosis and autophagy. In the present study, the dual-specific antitumor oncolytic adenovirus, Ad-Apoptin-hTERT-E1a (ATV), was used to infect cervical cancer cell lines to test its antitumor effects. Methods: To explore the use of apoptin in tumor gene therapy, a recombinant adenovirus ATV expressing the apoptin protein was assessed to determine its lethal and growth-inhibitory effects on human cervical cancer cell line (HeLa) cells in vitro . Nonapoptotic autophagy of HeLa cells infected with ATV was assessed by examining the cell morphology, development of acidic vesicular organelles and the conversion of microtubule-associated protein 1 light chain 3 (LC3) from its cytoplasmic to autophagosomal membrane form. Using gene silencing (knockdown of LC3 and Belin-1), autophagy-associated molecules (e.g. ATG5, ATG12 and ULK1) were monitored by real-time PCR and western blot. Results: A series of experiments demonstrated that ATV could significantly induce apoptosis and autophagy in cervical cancer cells, and provided evidence that ATV not only induced apoptosis but also autophagy and ATG5, ATG12 and ULK1 related pathways were not entirely dependent on LC3 and Beclin-1. Conclusion: These results indicate that ATV may have a potential application in tumor gene therapy.